A new species of Progonocimicidae (Hemiptera: Coleorrhyncha) from northeastern China - Dong, Qiuping; Yao, Yunzhi; Ren, Dong (Zootaxa, 2012)
A new fossil species, Cicadocoris varians sp. n., of the family Progonocimicidae is described from the Middle Jurassic Jiulongshan Formation of Daohugou Village, Inner Mongolia, China. This Progonocimicidae is a well-preserved unusual fossil showing different sizes and proportions of the left and right tegmen.